Etika Bisnis Divisi Pemasaran di PT. KC Softex Indonesia - Dini Yuniar Pratama; Amin Sadiqin (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2022)
Ethics is a person’s behavior for good or bad things through a witten or spoken. While business is an individual or organizational activity that creates a product or service with the intention of making a profit and meeting the needs of the community. The author’s purpose in making this article is to provide information about business ethics at PT. KC Softex Indonesia which are engaged in modern and traditional trade. This research method uses descriptive and normative analysis in order to get good and accurate information to understand the concept of business ethics at PT. KC Softex Indonesia. There are ethics that must be followed so that the business can run well and smoothly, such as building harmonious relationship between employees, superiors, and consumers.